Barrier for Charge Transfer at Liquid/Liquid Interface - Al-Agealy Hadi J. ,M; Al-Saadi Adil. A., M (Journal of Madenat Alelem University College, 2012)
Abstract The height potential barrier ∆G^(++) (eV) of charge transfer at liquid/liquid interface was described and calculated on the base of the semi classical theory. It is a function of the reorganization energy, and driving force energy respectively. Results of the reorganization energy E_0 indicate that the charge transfer is more probable in liquid/liquid system which has more polarity parameter. Charge transfer in system has large dielectric constant are stronger than system that have small dielectric constant. The driving force energy for charge transfer is the energy that takes to bring the donor and acceptor together and drive the charge increases with the increase of absorption energy and decrease in wave length. Results of height barrier ∆G^(++) (eV) across liquid/liquid interface decreases with the decrease of the driving force energy and increasing of the absorption energies. The transition is so much small as a barrier has large values but in the low values of barrier, the transfer is most probable. The large height barrier exclusion transfer across liquid/liquid system and the charge suffering much resistant to transfer.